2015
DOI: 10.1071/sr14234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tillage effects on soil quality of pastures in South Africa with indexing methods

Abstract: Soil quality of pastures changes through time because of management practices. Excessive soil disturbance usually leads to the decline in soil quality, and this has resulted in concerns about kikuyu (Pennisetum clandestinum)–ryegrass (Lolium spp.) pasture systems in the southern Cape region of South Africa. This study aimed to understand the effects of tillage on soil quality. The soil management assessment framework (SMAF) and the locally developed soil quality index for pastures (SQIP) were used to assess fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
1
17
0
1
Order By: Relevance
“…Similarly, non-significant changes in C content with land use were observed for CTL, GRL and HL (Table 2). This finding is also supported by Swanepoel et al (2015), who stated that soil quality, in particular soil OC, changes over time because of management practices, especially tillage.…”
Section: Effect Of Land-use Management On Soil Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, non-significant changes in C content with land use were observed for CTL, GRL and HL (Table 2). This finding is also supported by Swanepoel et al (2015), who stated that soil quality, in particular soil OC, changes over time because of management practices, especially tillage.…”
Section: Effect Of Land-use Management On Soil Propertiessupporting
confidence: 83%
“…In a study of savanna ecosystems in Botswana, Kgosikoma et al (2015) observed a strong dependency of soil OC on rainfall and herbaceous biomass, which has a profound effect on biological crust formation (Thomas et al 2011). Furthermore, Swanepoel et al (2015) noted that soil quality, particularly soil OC, changes through time because of management practices, especially tillage. For instance, cultivation was reported to have depleted former virgin soils of humic substances across semi-arid agro-ecosystems in South Africa with a potential of reducing C and nitrogen losses into the atmosphere (Kotzé et al 2016).…”
mentioning
confidence: 97%
“…(, , ) have identified physical, chemical and biological indicators that have a functional role in pasture systems in South Africa. Subsequently, a selection of seven soil quality indicators that conveyed the most useful information for determining soil quality status was determined (Swanepoel et al ., ) and evaluated (Swanepoel et al ., ). However, these studies did not relate soil properties to herbage yield.…”
Section: Introductionmentioning
confidence: 97%
“…The SMAF has also been successfully used in several other countries around the world [e.g., South Africa (Swanepoel et al, 2015), Ethiopia (Gelaw et al, 2015), Nepal (Kalu et al, 2015)]. The first SMAF application to Brazilian tropical soils was conducted by Cherubin et al (2016a), who verified that SMAF was effective for assessing SQ changes due to land-use change (LUC) for sugarcane expansion in the central-southern region.…”
Section: Introductionmentioning
confidence: 99%